Sosialisasi dan Penerapan Kompetensi Literasi Digital di MA AL-MUSTHOFA - Ertansyah Rizal Priadi Sumarna; Nabila Aprilia Ramdhani; Tegar Radiansyah Suparman; Neng Wafa Jahrotulhayya; Ervin Abdal Rasyid; Abdul Latif; Leni Fitriani (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2022)
With the development of the internet today, of course there are a lot of positive and negative things that are obtained, especially with the covid-19 outbreak, of course all activities run online from learning, shopping and so on, therefore internet users are increasing rapidly, so the purpose of this task is to our tik tok volunteers are assigned to provide guidance and understanding about the internet well, with prepared materials about hate speech and also provide special services needed by the intended partner, and for our group from class A with the name arithmetic 1 group with The beneficiaries of MA Al-Musthofa and the special requests requested are material services regarding: Microsoft Office and Canva as well as reinstalling Ma Al-Musthofa's labcom from the results of the pre-test and post-test of all the materials presented, showing that the material can be delivered properly with all value of Sig.(2-tailed) < 0.05.